Platelet‐rich Plasma in Meniscal Repair: Does Augmentation Improve Surgical Outcomes?. Issue 5 (May 2015) - Griffin, Justin W.; Hadeed, Michael M.; Werner, Brian C.; Diduch, David R.; Carson, Eric W.; Miller, Mark D.
Abstract: Background: Increased contact stresses after meniscectomy have led to an increased focus on meniscal preservation strategies to prevent articular cartilage degeneration. Platelet‐rich plasma (PRP) has received attention as a promising strategy to help induce healing and has been shown to do so both in vitro and in vivo. Although PRP has been used in clinical practice for some time, to date, few clinical studies support its use in meniscal repair. Questions/purposes: We sought to (1) evaluate whether PRP augmentation at the time of index meniscal repair decreases the likelihood that subsequent meniscectomy will be performed; (2) determine if PRP augmentation in arthroscopic meniscus repair influenced functional outcome measures; and (3) examine whether PRP augmentation altered clinical and patient‐reported outcomes. Methods: Between 2008 and 2011, three surgeons performed 35 isolated arthroscopic meniscus repairs. Of those, 15 (43%) were augmented with PRP, and 20 (57%) were performed without PRP augmentation. During the study period, PRP was used for patients with meniscus tears in the setting of no ACL reconstruction. Complete followup at a minimum of 2 years (mean, 4 years; range, 2‐6 years) was available on 11 (73%) of the PRP‐augmented knees and 15 (75%) of the nonaugmented knees. Clinical outcome measures including the International Knee Documentation Committee (IKDC) score, Tegner Lysholm Knee Scoring Scale, and return to work and sports/activities survey tools were completed in person, over the phone, or through the mail. Range of motion data were collected from electronic patient charts in chart review. With the numbers available, a post hoc power calculation demonstrated that we would have expected to be able to discern a difference using IKDC if we treated 153 patients with PRP and 219 without PRP assuming an alpha rate of 5% and power exceeding 80%. Using the Lysholm score as an outcome measure, post hoc power estimate was 0.523 and effect size was −1.1 (−2.1 to −0.05) requiring 12 patients treated with PRP and 17 without to find statistically significant differences at p = 0.05 and power = 80%. Results: There was no difference in the proportion of patients who underwent reoperation in the PRP group (27% [four of 15]) compared with the non‐PRP group (25% [five of 20]; p = 0.89). Functional outcome measures were not different between the two groups based on the measures used (mean IKDC score, 69; SD, 26 with PRP and 76; SD, 17 without PRP; p = 0.288; mean, Tegner Lysholm Knee Scoring Scale, 66, SD, 32 with PRP and 89; SD, 10 without PRP; p = 0.065). With the numbers available there was no difference in the proportion of patients who returned to work in the PRP group (100% [six of six]) compared with the non‐PRP group (100% [nine of nine]) or in the patients who returned to their regular sports/activities in the PRP group (71% [five of seven]) compared with the non‐PRP group (78% [seven of nine]; p = 0.75). Conclusions: Patients who sustain meniscus injuries should be counseled at the time of injury about the outcomes after meniscus repair. With our limited study group, outcomes after meniscus repair with and without PRP appear similar in terms of reoperation rate. However, given the lack of power and nature of the study, modest size differences in outcome may not have been detected. Future larger prospective studies are needed to definitively determine whether PRP should be used with meniscal repair. Additionally, studies are needed to determine if PRP and other biologics may benefit complex tear types. Level of Evidence: Level III, therapeutic study.